Pengaruh Etika Bisnis Islam Di Toko Ry. Lubis Panyabungan Dalam Meningkatkan Minat Beli Konsumen - Siregar, Erni Yusnita; Sulina, Sulina; Siregar, Nurintan (ISLAMIC BUSINESS and FINANCE, 2024)
This study aims to determine the influence of Islamic business ethics in increasing consumer buying interest in the RY store. Lubis Aek Galoga Panyabungan, Mandailing Natal. The problem in this study is the sales turnover at the RY store. Lubis, which has experienced a significant decline. Especially since 2018 to 2022, it has shown a continuous decline. This decline in sales turnover identifies a decline in consumer buying interest in making purchases at the RY store. The research location is at the RY store. Lubis Aek Galoga Panyabungan. The method used is quantitative with a statistical method, taking samples with a sampling technique, namely non-probability sampling. The research sample amounted to 87 respondents. The variables used are justice, honesty, and ihsan/generosity. This study uses primary data using quantitative analysis. The results of the study show that the honesty variable has a positive and significant effect with a value of 2,904 on consumer buying interest. Justice has a positive and significant effect with a value of 3,788 on consumer buying interest. The ihsan/generosity variable has an effect and is significant with a value of 11,887. simultaneously that Fcount 177.496 > 2.71 F table, then Ha is accepted and Ho is rejected. Therefore, it is stated that the independent variables covering justice, honesty, and ihsan/generosity simultaneously influence the consumer buying interest variable significantly.